Deciphering the Late Cretaceous‐Cenozoic Structural Evolution of the North Peruvian Forearc System. Issue 1 (26th January 2018) - Espurt, N.; Brusset, S.; Baby, P.; Henry, P.; Vega, M.; Calderon, Y.; Ramirez, L.; Saillard, M.
Abstract: The link between plate tectonics and the evolution of active margins is still an ongoing task to challenge since the acceptance of plate tectonic paradigm. This paper aims at deciphering the structural architecture and uplift history of the North Peruvian forearc system to better understand the evolution and the mechanics that govern the Late Cretaceous‐Cenozoic building of this active margin. In this study, we report surface structural geology data, interpretation of seismic reflection profiles, apatite fission track data, and the construction of two offshore‐onshore crustal‐scale balanced cross sections. The structure of the North Peruvian forearc system is dominated by an accretionary style with northwestward propagation of thrust‐related structural highs involving continental/oceanic basement rocks and off‐scrapped sediments. The thrust systems bound thick thrust‐top forearc depocenters mainly deformed by crustal normal to strike‐slip faults and thin‐skinned gravitational instabilities. The sequential restoration of the margin calibrated with apatite fission track data suggests a correlation between uplift, shortening, and plate convergence velocity during Late Cretaceous and Miocene. Pliocene‐Quaternary shortening and uplift of the coastal zone is rather related to the subduction of asperities during convergence rate decrease. The development of crustal normal to strike‐slip faulting and subsidence zones might be the consequence of slab flexure, local basal erosion along subduction fault, and/or oblique subduction associated with sediment loading control. We conclude that the evolution of the North Peruvian forearc system was controlled by subduction dynamics, strong sediment accumulation, and recent ridge subduction, and it recorded the orogenic loading evolution of the Andes over the Cenozoic. Key Points: The North Peruvian forearc system structure is driven by buried imbricate thrust systems bounding thrust‐top sedimentary depocenters The Late Cretaceous‐Cenozoic accretion and uplift of the forearc system was punctuated by zones of crustal normal to strike‐slip faulting The forearc system evolution was controlled by subduction dynamics, thick sediment accumulation, and bathymetric asperities